PELAKSANAAN SUPERVISI MANAJERIAL SEBAGAI UPAYA PENINGKATAN PROFESIONALIAS GURU DALAM PENGELOLAAN ADMINISTRASI - Purwanto, Purwanto (Jurnal Inovasi Pembelajaran di Sekolah, 2021)
There are still many teachers at SDN Bulu Lor Semarang City who are not able to manage administration well, from. This can be assessed from the following: (1) Only 50% of the teachers are not well prepared for the administration of learning; (2) Only 30% of the teachers do the administration after carrying out the lesson; (3) Only 40% of the teachers whose administration reports comply with the rules. The lack of administrative quality is one of the problems that must be overcome by the principal by carrying out managerial supervision in improving the administrative performance of educators in managing learning which in the end is expected to improve the quality of education. This study is intended to answer the following problems: 1) How is the implementation of principal managerial supervision in order to improve teacher professionalism in classroom administration management at SDN Bulu Lor Semarang City for the 2020/2021 academic year?. 2) Is there an increase in teacher professionalism in classroom administration management after the managerial supervision of the principal at SDN Bulu Lor Semarang City in the 2020/2021 school year? These problems are discussed through classroom action research which is carried out through 2 cycles with each cycle of stages being planning, action, observation and reflection. Lor Semarang City for the 2020/2021 academic year is carried out by providing guidance and direction to teachers on how to properly manage class administration through a discussion process and providing individual assistance and guidance for teachers to be able to make good classroom administration. 2) There is an increase in teacher professionalism in management of classroom administration after the managerial supervision of the principal at SDN Bulu Lor Semarang City in the 2020/2021 school year, this can be seen from the increase in the results of teacher professionalism in classroom administration management per cycle where in the first cycle there are 15 teachers or 63%, and in the second cycle there were 22 teachers or 88%. These results indicate that these results are in line with expectations.